Determining the Suitable Location of Constructed Wetland for the Polluted River Water Treatment Based on Analytical Hierarchy Process and Geographic Information System Analysis - Mahendra, Daniel Rizal; Harmayani, Kadek Diana; Jaya, Ni Made Pertiwi; Widhiawati, Ida Ayu Rai; Bhaskara, I Gusti Agung Gede Wiranata; Supriyani, Nyoman Dewi; Hutagalung, Debora Sofia Fransiska; Nagai, Masahiko (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
The Tukad Badung River is a vital raw water source in Denpasar City and Badung Regency. Concerning the water pollution of the river, water treatment is necessary to manage the water quality. Constructed wetlands are a water treatment technology used for water purification. In this regard, information is essential regarding the appropriate location for the placement of the constructed wetland based on criteria related to the water treatment plant. The research was conducted to determine the suitability level of water treatment locations in the watershed using the Analytic Hierarchy Process method in integration with a Geographic Information System. The Geographic Information System analysis included overlaying steps of the processed and classified data from each criterion: land use, slope, and water pollution index. The Analytic Hierarchy Process method was carried out to obtain the weight of each criterion down to the sub-criteria, which were compiled through interviews with three informants from academic, government, and community representatives. Weight calculations were performed using Expert Choice 11 software to obtain weight values with a consistency ratio of < 0.1. Geographic Information System analysis using the Analytic Hierarchy Process method produces three suitable land types according to the level of suitability for water treatment locations, with constructed wetlands located in the upstream, middle, and downstream parts of the river. Information regarding suitable land is useful for planning the technical design of water treatment plants with constructed wetlands.